DAMPAK KRISIS GLOBAL TERHADAP NON PERFORMING LOAN BANK DEVISA NASIONAL - Suharyono Suharyono; Teguh Widodo (Inovbiz: Jurnal Inovasi Bisnis, 2016)
Abstract: The global crisis has resulted non performing loan (NPL) increased. The measurement of the banks non performing loan ratio is applicable to assess the composite rating of a bank, as the impact of the global crisis toward non performing loan of foreign exchange banks. This study aimed to determine whether there was significant difference between foreign exchange banks non- performing loan before and after the global crisis. The Bank’s non performing loans   was measured by comparing the Non-Performing Loan to the total credit. The population of this study was 35 foreign exchange  banks.   The Hypothesis was tested by using Mann Whitney  different test and Independent Sample T Test. The research of this study showed that non performing loan of foreign exchange banks before, during, and after global crisis did not have significant difference. Key words: NPL, Bank, Foreign Exchange, Crisis, global.